Anonychia and absence/hypoplasia of distal phalanges (Cooks syndrome): report of a second family. Issue 8 (August 1995) - Nevin, N C; Thomas, P S; Eedy, D J; Shepherd, C
Abstract : We describe a second family with four affected members in three successive generations with a rare nail dysplasia syndrome. The syndrome, which was first reported by Cooks et al in 1985, is characterised by bilateral nail hypoplasia of digits 1-3, with absence of nails of digits 4-5 of the hands, and total absence of all toe nails. In addition, there is absence/hypoplasia of the distal phalanges of the hands and feet. Our family confirms this syndrome as a distinct entity with autosomal dominant inheritance.